2015
DOI: 10.1016/s2352-3018(14)00034-4
|View full text |Cite
|
Sign up to set email alerts
|

Linkage to and engagement in HIV care in western Kenya: an observational study using population-based estimates from home-based counselling and testing

Abstract: Summary Background There is limited research characterizing the HIV care continuum with population-based data in sub-Saharan Africa. The objectives of this study were to: 1) describe engagement in care among all known HIV-positive adults in one sub-county of western Kenya; and 2) determine the time to and predictors of linkage and engagement among adults newly diagnosed via home-based counseling and testing (HBCT). Methods AMPATH (Academic Model Providing Access to Healthcare) has provided HIV care in weste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
82
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(91 citation statements)
references
References 38 publications
8
82
1
Order By: Relevance
“…This was probably due to the already high (89%) level of linkage to care in the standard‐of‐care (referral only) arm of that trial. In contrast, linkage to care in our standard‐of‐care arm was 33%, a figure consistent with that observed after routine referral in previous studies 20, 30, 31, 38, 39, 40.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This was probably due to the already high (89%) level of linkage to care in the standard‐of‐care (referral only) arm of that trial. In contrast, linkage to care in our standard‐of‐care arm was 33%, a figure consistent with that observed after routine referral in previous studies 20, 30, 31, 38, 39, 40.…”
Section: Discussionsupporting
confidence: 91%
“…On the basis of findings from HBHCT studies in which only referral was provided following HIV diagnosis 30, 31, 32, 33 and those in which counselling was provided after referral 6, 7, we assumed linkage of 35% in the control arm and that this would increase to 60% in the intervention arm. We aimed to have 80% power to detect this increase at a significance level of 5%.…”
Section: Methodsmentioning
confidence: 99%
“…These linkage-to-care results (49% at 3 months) are in line with other studies conducted in sub-Saharan Africa using home-based [26,27] and other testing strategies [6]. Our study adds to the evidence base that home-based testing strategies are effective to diagnose and link to care remaining undiagnosed individuals in a population where an already high proportion is diagnosed, but also underscores that more attention is needed to support timely linkage to care.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to other studies, we found that young HIVpositive adolescents and young adults (age [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] were less likely to be diagnosed and to link to care once diagnosed. Survey data collected from sub-Saharan Africa indicate that only 10% of young men and 15% of young women (15-24 years) were aware of their HIV status [34].…”
Section: Discussionsupporting
confidence: 87%
“…9 Our work in the Academic Model Providing Access to Healthcare (AMPATH) programme in western Kenya shows high levels of HTC coverage, but suggests linkage rates might be low if not actively facilitated. 10 Ying and colleagues write about an encouraging intervention in a catchment area where HTC had very high coverage and linkage to care was strong because of the geographical proximity of care facilities. 1,11 Although frequency of HTC plays a part, the main focus of the analysis by Ying and colleagues is a comparison of ART initiation thresholds under an assumption of high rates of linkage to care.…”
Section: Home Testing and Counselling With Linkage To Carementioning
confidence: 99%